Law nº 14.285/21: Law after the Forestry Code and less protective of the environment (PerCursos, 2024)
Law nº 14,285/21 has empowered Brazilian municipalities to regulate permanent preservation areas (PPAs) near watercourses in urban areas. Resolution CONSEMA nº 196/22 further detailed the matter, based on the opinion of the Public Ministry and two notes from the Federation of Consortia, Associations, and Municipalities of Santa Catarina. This legislative amendment is the subject of Direct Action of Unconstitutionality (Adin) nº 7,146/22 in the Federal Supreme Court (STF). In this process, the debate revolves around whether municipalities have the authority to regulate the matter or if it falls under the jurisdiction of the Union. The principle of checks and balances between the branches of government is also discussed, emphasizing that the legislature should not act subsequently and in discordance with an issue already decided by the judiciary. Finally, the necessary adherence to the principle of non-regression in environmental protection is underscored. In addition to the discussion in the STF, Law nº 14,285/21 altered the concept of consolidated urban areas, assigning to municipalities the responsibility of locally scoring these areas, facilitating the "selection" of PPAs near watercourses in urban areas. This situation opens the door to real estate speculation. The justification for this law project itself reflects concerns about consolidated areas, regardless of whether they are areas of social interest. This scenario will be exemplified by the current situation in the municipality of Joinville, Santa Catarina. Thus, Resolution CONSEMA No. 196/22, the debate on the unconstitutionality of Law nº 14,285/21, and the legislator's intention, as stated in the justification of Law nº 14,285/21, will be analyzed, illustrating this reality with the current situation in Joinville.
Keywords: permanent preservation area; forest code; legislative competence